PREVALANCE OF SECOND MESIOBUCCAL CANAL IN MAXILLARY SECOND MOLARS ON THE BASIS OF CLINICAL AND RADIOGRAPHIC PARAMETERS - Akbar, Iftikhar; Junaid Islam; Abdul Majeed; Rizwan Qureshi (Journal of Ayub Medical College Abbottabad, 2023)
Background: The objective of this study was to determine the prevalence of the second mesiobuccal canal in permanent maxillary second molar in patients presenting to Peshawar Dental College and Hospital. Methods: One hundred and twenty patients advised for root canal treatment in the maxillary second molars participated in the study. Two detection procedures, clinical and radio graphical examination were used. Two pre-operative radiographs with different angulations and one post-operative radiograph were taken to examine roots and root canals. Access cavities were prepared and the second mesiobuccal canal was explored using magnifying dental loupes (3.5 x), endodontic explorer (DG16) and size 10 K-file. Descriptive statistics were recorded as percentages, frequencies and mean. The chi-square test was used for gender, age-wise comparison and right and left side of the maxillary jaw. Results: One hundred and twenty patients were recruited in the study. There were 65 (54.2%) males and 55 (45.8%) females. The second mesiobuccal canal was more common in males compared to females (p-value=0.434). The second mesiobuccal canal was most commonly found in 3rd decade with mean age, of 40.5±12.31, (p-value =0.51). The frequencies and percentages of the second mesiobuccal canal in maxillary second molars on the right and left side of the jaw were 70 (58.3%) and 50 (41.7%) respectively (p-value =0.310). Conclusion: The second mesiobuccal canal was found in less than half of the second molars. The most successful method of detection in this study was both clinical and radiographic.